Imuno-expressão das proteínas da família BCL-2 (BCL-2. BCL-XL, BAX, BAK, BAD) em câncer gátrico, preparados em arranjo em matriz (TMA) - Barrezueta, Luis Fernando Mesias [UNIFESP] (2009)
Purpose: To study the immunoexpression of Bcl-2 family proteins (Bcl-2, Bcl-xl, Bax, Bak, Bad) and to evaluate the correlation between the immunoexpression of these proteins with the cleaved caspases 3, Ki-67 and p53 immuno-expression. Methods: A TMA paraffin block was constructed with gastric carcinoma tissue (test group) and normal gastric adjoining mucosa (control group) of 87 patients. The TMA block was submitted to immunohistochemistry for Bcl-2, Bcl-xl, Bax, Bak, Bad, p53 and-cleaved Caspase 3. Results: All studied proteins were present in tumor and normal gastric adjoining mucosa, but with different intensity and amount of positive cells. i) There was an association between tumor size and p53 expression. ii) association between Bad expression in the tumor and patient’s age. iii) Intestinal type adenocarcinoma was positively correlated with the expression of Bax, Bad and Ki-67. iv) The protein Bcl-xl, Bak, Bad, p53 and Ki-67 showed statistically significant differences between the immuno-expression in tumor and normal gastric adjoining mucosa. v) There was an association between the proteins Bax, Bak and Bad expression in the normal gastric adjoining mucosa. vi) No correlation between patient’s survival rates and the expression of the proteins was observed. Conclusions: The higher expression of Bcl-xl protein in adenocarcinoma, the difference of Bcl-xl expression between test group and control group, might be related with the anti-apoptotic effect of this protein. The lower expression of Bak and Bad and the increased expression of p53 protein and Ki-67 protein in adenocarcinomas demonstrate the imbalance between death and cellular proliferation, which allows the uncontrolled tumor cell proliferation.